อุบัติการณ์ของผื่นแพ้ยาในผู้ป่วยที่ติดเชื้อเอชไอวีในโรงพยาบาลจุฬาลงกรณ์ - วิรัช รุจิแสงวิทยา (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This is the study of incidence of cutaneous drug eruptions of HIV-infected patients in Chulalongkorn Hospital by collecting of data for 1 1/2 years from June 1, 1998 to November 30, 1999. The target populations were HIV-infected patients in Chulalongkorn Hospital during the above period. Medical histories, physical examinations and laboratory investigations were performed in each patient who was diagnosed as cutaneous drug eruption. Oral rechallenge tests with suspected drugs were performed in all cases who had no contraindication for identifying the definite causative drugs. "An alorithm for the operational assessment of adverse drug reactions" was used for diagnosing cutaneous drug eruptions and identifying the causative agents. There were 90 HIV-infected patients who were diagnosed as cutaneous drug eruptions. The incidence of cutaneous drug eruptions in HIV-infected patients was 1.21%. The incicence of cutaneous drug eruptions was 48.4 times greater in HIV-infected patients than in the general patients of Chulalongkorn Hospital that previously reported from December 1995 to May 1997. The three most common types of cutaneous drug eruptions were maculopapular rash, eryhtherma multiforme, and Stevens-Johnson syndrome, respectively. Trimethoprim-sulfamethoxazole was found to be the most common causative drug of all types of cuateneous drug eruptions except photoallergic drug equption. The likelihood of developing a cutaneous drug eruption in HIV-infected patients was increased according to the advancing stage of HIV infection and decreasing CD4+cell counts.